Postcolonial Representation in the Novel Janji Tanah Jawa by Agil Sri Rahayu: - Suswarini; Laila Tri Lestari; Khoirul Huda (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Postcolonial representation in the novel Janji di Tanah Jawa by Agil Sri Rahayu depicts traces of colonialism through identity, culture, and power relations in people's lives. This study aims to describe the forms of postcolonial representation contained in the novel Janji di Tanah Jawa by Agil Sri Rahayu. The method used in this study is a qualitative descriptive method with a postcolonial study approach. Through this method and approach, the research data is described from a colonial perspective in the novel Janji di Tanah Jawa, resistance to colonial power, and the representation of cultural identity and characters in the colonial structure. The research data in the form of quotations in the novel were collected using a non-test instrument, namely observation guidelines based on time triangulation. Postcolonial representation in the novel Janji di Tanah Jawa by Agil Sri Rahayu was analyzed thematically using a content analysis technique approach based on time triangulation through a check-check guide sheet both for the data collection process and in the data analysis process of postcolonial representation in the novel Janji di Tanah Jawa by Agil Sri Rahayu. The analysis of postcolonial representation in Agil Sri Rahayu's novel Janji di Tanah Jawa (Promise in the Land of Java) demonstrates postcolonial aspects through the dominance of power, cultural hybridity, the search for identity, and the characters' resistance to colonial legacies. These findings demonstrate that the novel not only depicts historical events but also reflects the impact of colonialism on the social and cultural life of Indonesian society.